EFEKTIFITAS PERMAINAN LAYANG-LAYANG UNTUK MENINGKATKAN KECEPATAN BERLARI BAGI ANAK TUNAGRAHITA SEDANG - Rani Permata Sari; Ardisal Ardisal; Fatmawati Fatmawati (Jurnal Penelitian Pendidikan Khusus, 2013)
ABSTRACTThis study originated from the observation that the author did in the 20 State SDLB cottage Duo, met tunagrahita underprivileged children in doing gross motor movement ran over her other friends. This study aims to prove that by playing a kite child can improve gross motor skills tunagrahita child ran in the State 20 SDLB cottage Duo. Research subjects were the children mental retardation were sitting in class IIC. This type of research is the Single Subject Research methods look towards trends graph that compares the Baseline condition, the condition given treatment after treatment and were not given a second baseline treatment. Procedures perekapan procedure data by direct observation of the results of the game kite given to children to improve gross motor skills children ran tunagrahita. The data is taken directly in kekgiatan noting how long the duration of the child's ability to run from start to finish 20 meters distance. The results are analyzed include the number of observations in the baseline condition as much as seven times, seven times as many treatment conditions and baseline second four times. Results of this study indicate that the kite through the game can improve gross motor skills ran significantly. This is evident from the analysis of the trend towards increased. In the baseline condition of gross motor skills children ran to get the highest percentage of 40%. After a given treatment with proven games or kite gross motor skills children ran up the highest percentage of children obtaining results 100%. The researchers suggest to teachers to implement learning with game-kite serviceability to improve gross motor running for future learning.Kata kunci: Anak tunagrahita sedang; kecepatan berlari; penerapan permainan layang-layang.